Efeitos quimioprotetivos do flavonoide hesperidina contra mutagenicidade induzida por cisplatina em medula óssea de camundongos - Passos, Tatiane da Silva (2013)
Hesperidin is a flavonoid naturally found in citrus fruit especially orange and lemon peel. We investigated the antimutagenic activity of this compound against the cytotoxic and mutagenic effects induced by the anticancer drug cisplatin (CddP) using the micronucleus assay in bone marrow erythrocytes of mice (Mus musculus). We used three protocols: pre-treatment with hesperidin (by gavage) for 14 days, followed by applying (intraperitoneally) from CddP no 14th day; Post-treatment administration of CDDP and 24 hours after the administration of hesperidin and simultaneous treatment with hesperidin and CddP. We evaluated three concentrations of Hesperidin diluted in corn oil (100mg.kg-1, 200mg.kg-1 e 400mg.kg- 1). The controllling was conducted by the negative control (NaCl 0,9%), positive control (CddP 0,05mg.kg-1) and and the solvent controls (corn oil). For micronucleus test, the animals were euthanized 24 hours following the last treatment by cervical dislocation, and bone marrow was collected. The samples were transferred to Falcon tubes and centrifuged. Slides were prepared by smear technique with a drop of suspension and fixed with methanol for 10 minutes, staining was performed with Leishman stain. The reading was performed in blind test, we analyzed 2000 cells per animal in an optical microscope for evaluation of micronucleated polychromatic erythrocytes (MNPCEs) and the ratio PCE/(PCE+NCE) (polychromatic erythrocytes/polychromatic erytrocites + normochromatic erythrocytes). All protocols studied showed a reduction in the number of micronuclei when compared to CP and achieved high rates of reduction of damage caused by cisplatin, except the concentration of 400 mg.kg-1 of the simultaneous treatment protocol where such protective effect was not observed indicating that hesperidin has chemoprotective action on the DNA molecule. It is known that various flavonoids have the ability to eliminate free radicals such as hydroxyl radicals generated by chemical agents that cause DNA damage, but the exact mechanism of how hesperidin acts is not yet clear.